PENGARUH STABILISASI ABU DAUN BAMBU DAN SEMEN TERHADAP KEMBANG SUSUT (SWELLING) TANAH LEMPUNG EKSPANSIF - Wijaya, William (Jurnal Teknik Sipil, 2021)
Soft clay is a soil type mostly found in Indonesia. This type of soil requires treatment because of its poor properties. These properties have a relatively low bearing capacity in water saturated conditions, high swelling potential, and high plasticity. These are several methods to improve clay soil, including soil stabilization. Soil stabilization is a method of mixing pozzolanic materials such as cement and bamboo leaf ash with the natural soil. The purpose of this addition is to reduce the characteristics of expansive clay such as high swelling potential. The research focused on the results of swelling testing using an oedometer test and was carried out using 6 sample variants using cement with a percentage of 12% of the dry mass of soil and bamboo leaf ash with a percentage of 0%, 25%, 50%, 75%, 100% of the total weight of cement used. Preliminary research is carried out before the core research. The research included examining the original soil parameters, mineral content, and pozzolanic content of bamboo leaf ash. The results of the preliminary research showed that the natural soil is classified as a high plasticity (CH) clay group and had a high potential for swelling and shrinkage. Whereas in the pozzolanic material test, bamboo leaf ash contained a chemical compound of SiO2 as much as 79.68%. Based on the results, cement and bamboo leaf ash as stabilization agents succeeded in reducing the swelling value of the soil from 15.71% to 4.33% in the S100ADB0 and 6.07% variations in S75ADB25.